Stress Ibu dengan Anak Usia Sekolah di Masa Pandemi COVID-19 - Arnindya Kanti Prasasti; Widyatuti; Astuti Yuni Nursasi (STIKES Ngesti Waluyo, 2022)
The COVID-19 pandemic has brought various changes to people's lives as well as created stressors in various aspects of life. The mothers with school-aged children could feel quite heavy stress, because at that age the child already has his own desires but does not yet have the autonomy so that the mother must exercise a tight control. This study aims to determine the description of stress in mothers with school-aged children during the COVID-19 pandemic. The research design used was quantitative research with analytical descriptive method. The sampling method was probability sampling with cluster sampling. After analysing the data, the results showed that the general stress variable for mothers was classified as mild with a mean of 0.83 and a standard deviation of 0.77, with a minimum and maximum value of 0 and 5. Meanwhile, specific stress was classified as high, with a mean of 3.95 with a standard deviation. 0.72, and a minimum-maximum value of 1-5. Further analysis showed that the specific stress which appears on mothers is mostly caused by economic difficulties (30.3%) and accompanying children during online school (41.8%). This study is expected to provide an overview for nurses about the stress experienced by school-age mothers and their risk factors.